Resident interaction and social well-being in an oil boomtown in western North Dakota. Issue 4 (1st December 2018) - Archbold, Carol A.; Mrozla, Thomas; Huynh, Carol; Dahle, Thorvald O.; Robinson, Chloe; Marcel, Alexandra
Abstract: Previous studies on the social well-being of residents living in energy boomtowns focus primarily on demographic characteristics of residents. These studies do not consider that there could be a relationship between residents' social well-being and whether they interact with new residents moving into their community. The current study includes a measure of interaction with new residents as it examines five dimensions of the social well-being of residents living in an oil boomtown in western North Dakota. Surveys were distributed door-to-door to residents living in Williston North Dakota during the fall of 2015. Research findings show that people who reported that they interact with new residents moving into their community felt safe from crime and violence in their community; felt more socially integrated in their community; had high levels of community trust and community satisfaction, and believed that they could count on their neighbors. These findings are important because they highlight the significance of social interaction in communities that experience rapid population growth resulting from increased energy production.